2020
DOI: 10.1097/brs.0000000000003861
|View full text |Cite
|
Sign up to set email alerts
|

Association of Duration of Preoperative Opioid Use with Reoperation After One-level Anterior Cervical Discectomy and Fusion in Nonmyelopathic Patients

Abstract: Study Design. Retrospective cohort study.Objective. The aim of this study was to determine that rates of preoperative opioid use in patients undergoing single-level anterior discectomy and fusion (ACDF) without myelopathy and determine the association with reoperations over 5 years Summary of Background Data. Preoperative opioid use before cervical spine surgery has been linked to worse postoperative outcomes. However, no studies have determined the association of duration and type of opioid used with reoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Similarly, patients with prolonged opioid use and increased opioid requirements are more likely to experience reoperations, readmissions, complications, and increased cost of care. 32,33…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, patients with prolonged opioid use and increased opioid requirements are more likely to experience reoperations, readmissions, complications, and increased cost of care. 32,33…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, patients with prolonged opioid use and increased opioid requirements are more likely to experience reoperations, readmissions, complications, and increased cost of care. 32,33 Even among opioid-naïve patients, PCF still led to significantly greater opioid use in the short-term postoperative period. In addition, persistent opioid prescriptions were significantly more likely if patients were prescribed opioids within 1 month of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Hills et al reported that chronic users were less likely to return to work by 1 year and had an increased 90-day complication rate compared with those without chronic preoperative opioid use, controlling for disability scores, depression, anxiety, and other covariates that may affect return-to-work and complication rates 16 . Reoperation rates were also lower in opioid-naive patients at 5 years after one-level anterior cervical discectomy and fusion (ACDF) surgery (4.7%) compared with chronic preoperative users of tramadol (25%), hydrocodone (15.5%), or oxycodone (23.3%) 13 . Of note, acute use of any 3 of those opioids was not associated with reoperation.…”
Section: Methodsmentioning
confidence: 99%
“…For patients with spine pathology considering surgery, increasing evidence suggests that preoperative opioid use negatively affects outcomes after spine surgery 7 . It is estimated that the rate of spine patients considering surgery on opioids perioperatively ranges from 20% to greater than 60% [8][9][10][11][12][13] . Understanding how to optimize these patients for surgery through preoperative weaning periods and maximum dose thresholds will be crucial in improving patient outcomes.…”
mentioning
confidence: 99%
“…Postsurgical outcome measures of major interest to spine surgeons and patients include postoperative pain and narcotics utilization. [10][11][12][13][14] These variables are especially important to consider for ambulatory procedures, 15 such as lumbar microdiscectomy, since they may dictate case order, possible overnight admission, and outpatient opioid prescriptions. Currently, data on clinical utility of preoperative PROMIS-PF in predicting immediate postoperative pain, narcotics consumption, and other long-term PROMs after lumbar microdiscectomy is lacking.…”
Section: Introductionmentioning
confidence: 99%